2019
DOI: 10.1093/tcbh/hwz008
|View full text |Cite
|
Sign up to set email alerts
|

‘You Can’t Dismiss that as Being Less Happy, You See it is Different’. Sexual Counselling in 1950s England

Abstract: This article uses the audio recordings of sexual counselling sessions carried out by Dr Joan Malleson, a birth control activist and committed family planning doctor in the early 1950s, which are held at the Wellcome Library in London as a case study to explore the ways Malleson and the patients mobilised emotions for respectively managing sexual problems and expressing what they understood as constituting a ‘good sexuality’ in postwar Britain. The article contains two interrelated arguments. First, it argues t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…More recent historical scholarship disputes these claims. Rusterholz (2019Rusterholz ( , 2021Rusterholz ( , 2022 has shown that mid-century sexual counselling called on individuals to work actively, stoically and responsibly towards achievement of the emotional openness perceived as necessary to mutual sexual satisfaction in stable heterosexual relationships. This research confirms and extends the analysis of Chettiar (2016), who sees the state-sponsored expansion of marriage counselling and debates on divorce reform as two sides of the same coin; both demonstrate the identification of romantic and sexual relationships, underpinned by psychologised concepts of emotional health, as essential to social stability.…”
Section: Original Researchmentioning
confidence: 99%
“…More recent historical scholarship disputes these claims. Rusterholz (2019Rusterholz ( , 2021Rusterholz ( , 2022 has shown that mid-century sexual counselling called on individuals to work actively, stoically and responsibly towards achievement of the emotional openness perceived as necessary to mutual sexual satisfaction in stable heterosexual relationships. This research confirms and extends the analysis of Chettiar (2016), who sees the state-sponsored expansion of marriage counselling and debates on divorce reform as two sides of the same coin; both demonstrate the identification of romantic and sexual relationships, underpinned by psychologised concepts of emotional health, as essential to social stability.…”
Section: Original Researchmentioning
confidence: 99%
“…From the interwar years onwards, in the field of sexual counselling and marriage relationships, the expression of emotions held a significant role in the understanding of the fragility of relationships, sexual development and sexual dysfunctions. The idea that emotions and authenticity were key to successful relationships were spread by marriage and sexual reformers, the Marriage Guidance Movement, church organisations, the FPA and agony aunts and advice columns in magazines and newspapers, among others (Chettiar 2013;Collins 2006;Harris 2015;Langhamer 2015;Langhamer 2013;Lewis, Clark, and Morgan 1992;Rusterholz 2019). BAC's work did draw on this tradition and represented a departure from it, since BAC applied it to advising young people, a clear break from the interwar focus on married people.…”
Section: Emotional Labour Navigating Values and The Model Of Good Sexualitymentioning
confidence: 99%
“…Thus, for the first time, the notion of enjoyment and pleasure was finally connected to that of young people. Indeed, while sexual pleasure became increasingly discussed and central to the sexual life of married couples from the interwar years onwards (Rusterholz 2019), and thus became a new field of practice in FPA clinics, associating sexual pleasure with young people was still highly controversial since it was feared it would encourage promiscuity. Sex education in school, when not simply absent, focused mainly on combatting venereal diseases; sexual pleasure was never addressed.…”
Section: Psychosexual Counselling Pleasure and Gendered Sexual Rolesmentioning
confidence: 99%
“…Studies on marriage guidance and sex therapy have shown that an analysis of counselling encounters may teach historians much about the cultural diffusion of norms regarding gender and sexuality. 6 More specifically, Carolyn Herbst Lewis has used psychiatric evaluations and personal interviews for AID as a lens through which to examine masculinity in post-war American society. In her view, discussions of artificial insemination revealed an abiding concern for appropriate heterosexual gender identification and role fulfilment -especially for men.…”
mentioning
confidence: 99%